The Solution to Overcome Conflicts in the Protection of Trademarks and Trade Names - Thi Thanh, Dang; Quang, Nguyen Nhat (VNU Journal of Science: Policy and Management Studies, 2020)
Abstract : The objective of this paper is to propose solutions to overcome conflicts between industrial property rights over trademarks and industrial property rights over trade names. The research tasks consist of: Identifying the cause and the nature of the conflict, the mechanism to deal with the conflict under Vietnam current law; Pointing out unresolved issues in that mechanism, comparing with intellectual property law and practice of other countries to look for proper solutions for Vietnam.